A Joint Limit Theorem for Laplace Transforms of the Riemann Zeta–Function - Laurinčikas, A. (Nonlinear Analysis: Modelling and Control, 2007)
In the paper, a joint limit theorem in the sense of weak convergence of probability measures on the complex plane for Laplace transforms of the Riemann zetafunction is obtained.